1991
DOI: 10.1007/bf02390176
|View full text |Cite
|
Sign up to set email alerts
|

Primary glial tumor patients treated by combining cis-platin and etoposide

Abstract: Thirty eight patients with malignant gliomas (27 GBM and 11 AA) were treated with up to 7 cycles of CDDP + VP16 every month after surgery. Chemotherapy was planned as two cycles before and 5 cycles after radiation (42 Gy) using a three times daily fractionation schedule. No severe toxicity was observed. The object of our study was to investigate the antitumor effectiveness by combining CDDP plus VP16 against primary malignant glial tumors. The time to tumor progression (TTP) and survival time (ST) of the GBM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Because ⌬EGFR expression in glioma cells has been shown to decrease the rate of apoptosis both under serum-starved culture conditions and in implanted tumors derived from such cells (16), we tested the sensitivity of ⌬EGFR-expressing glioma cells to the chemotherapeutic drug, CDDP, a DNA-damaging agent known to induce apoptosis in tumor cells and that often has been used in glioma therapy (21,22). Endogenous and exogenous wt EGFR were moderately autophosphorylated under the culture condition used (10% serum), suggesting that wt EGFR was constantly stimulated by ligand in the serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because ⌬EGFR expression in glioma cells has been shown to decrease the rate of apoptosis both under serum-starved culture conditions and in implanted tumors derived from such cells (16), we tested the sensitivity of ⌬EGFR-expressing glioma cells to the chemotherapeutic drug, CDDP, a DNA-damaging agent known to induce apoptosis in tumor cells and that often has been used in glioma therapy (21,22). Endogenous and exogenous wt EGFR were moderately autophosphorylated under the culture condition used (10% serum), suggesting that wt EGFR was constantly stimulated by ligand in the serum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore wanted to determine whether it was more effective in vitro if administered in combination with a cytotoxic agent that could retard the proliferation of the tumor cells. We chose to use CDDP because this compound has been used in the clinical treatment of GBM (19,27,28). We first tested the ability of Å6 to directly inhibit the in vitro proliferation of a panel of GBM cell lines that included U87MG, U251MG, U178MG, LN229, A1207, and LNZ308.…”
Section: å6 Inhibits Hmvecs' Migration But Not Their Proliferation Ormentioning
confidence: 99%
“…A recent study showed the activity of a CBCDA (carboplatin) -VP-16 (etoposide)-based therapy in the treatment of low-grade gliomas in children (Massimino et al, 2002). The efficacy of CBCDA or cisplatin (CDDP) in combination with etoposide has been evaluated in various schedules in other trials in high-grade gliomas with various results (Buckner et al, 1990;Boiardi et al, 1991;Jeremic et al, 1992). The role of topoisomerase IIa in glioma cancer cells is still unclear.…”
mentioning
confidence: 99%